The main features of the formation of a sense of patriotism in the family in students - Rakhmonov Azamat Ruzvonovich (Zien Journals, 2022)
the article points to the fact that the right organization of the life of children in family education is the main guarantee of their correct and productive use of time, parents should educate their children
Keywords: family problems; family stability; he right organization of the life of children in family education; issues of Family Education